The Investigation of Financial Reporting Practices Among Legal Established Small Medium-Sized Enterprises in Pontianak - B1034141022, Dewi Meliawaty (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The aim of this study is to investigate the financial reporting practices among legal SMEs in Pontianak. This research use decriptive analysis method and investigated 187 SMEs by direct and indirect interview and self-answered questionnaire. Findings shows that 58% of SMEs in Pontianak prepare financial statements with 22% and 36% respectively prepares the complete four set with computerized and incomplete financial statement with manual accounting system. The computerized SMEs record keeping is in accordance with accounting cycle while the manual system was not. Most of the SMEs mentioned that they face no obstacles in preparing financial statement. SMEs in Pontianak prepared bookeeping and financial statement in simple form based on their understanding toward the accounting and facility they have.Â Keywords: Four-set financial statement, computerized accounting system, manual accounting systemÂ Arifin, Nurul. (2017). â€œAduh! Masih Banyak Pelaku UMKM Buta Laporan Keuanganâ€. Accessed on 6 February 2018 at 14.12 https://economy.okezone.com/read/2017/05/23/320/1698304/aduh-masih-banyak-pelaku-umkm-buta-laporan-keuanganÂ Asaduzzaman, Md. (2016). â€œAccounting and Financial Reporting Practices of SMEs: Bangladesh Perspectiveâ€. Malaysian Journal of Business and Economics Vol. 3 No. 1Â Astarani, Juanda and Yosica. (2015). â€œPersepsi Lembaga Pemberi Modal Terhadap Kualitas Laporan Keuangan UMKM Kota Pontianakâ€. JAAKFEÂ Bapage, Claudia Elsa. (2017). â€œAnalysis of Understanding of Accounting Students Towards Basic Concepts of Accountingâ€. Thesis. Accounting Department, Economic and Business Faculty of Tanjungpura University Pontianak.Â Barreiro, Paula Lagares and Albandoz, Justo Puerto. (2001). â€œPopulation and Sample. Sampling Techniquesâ€. Management Mathematics for European SchoolsÂ Bouri, Amit; Breij, Mark; Diop, Magatte; Kempner, Randall; Klinger, Bailey and Stevenson, K. (2011). Report on Support to SMEs in Developing Countries through Financial Intermediaries. DALBERGÂ Dyt, Robyn; and Halabi, Abdel K. (2007). â€œEmpirical Evidence Examining the Accounting Information Systems and Accounting Reports of Small and Micro Business in Australiaâ€. Small Enterprise Research 15, 2Â Ezeagba, Charles. (2017). â€œFinancial Reporting in Small and Medium Enterprises (SMEs) in Nigeria: Challenges and Optionâ€. HRMars: International Journal of Academic Research in Accounting, Finance and Management Sciences Vol. 7 No. 01.Â Faridah, Titik. (2015). â€œPenyusunan dan Pengungkapan Laporan Keuangan Usaha Kecil dan Menengah Berdasarkan SAK ETAPâ€. Thesis. Accounting Department, Economic and Business Faculty of Universitas Brawijaya Malang.Â Harahap, Sofyan Syafri. 2010. Analisa Kritis atas Laporan Keuangan. Jakarta: PT RajaGrafindo PersadaÂ Hendry. (2012). â€œMenentukan Ukuran Sampel Menurut Para Ahliâ€. Accessed 7 June 2018 at 12:20 https://teorionlinejurnal.wordpress.com/2012/08/20/menentukan-ukuran-sampel-menurut-para-ahli/Â http://goukm.id/apa-beda-situ-dan-siup/Â http://pontianak.tribunnews.com/2018/01/11/fasilitasi-umkm-pemerintah-launching-aplikasi-sipi-kalbar-ada-display-juga-lohÂ http://www.accountingverse.com/accounting-basics/types-of-businesses.htmlÂ http://www.etrade.id/2016/05/umkm-definisi-kasifikasi-dan-contohnya.htmlÂ http://www.pontianakpost.co.id/pontianak-bangun-gedung-umkmÂ https://dosenekonomi.com/bisnis/peluang-bisnis/jenis-usaha-mikro-kecil-dan-menengahÂ https://en.oxforddictionaries.com/definition/legalÂ https://pontianakkota.bps.go.id/dynamictable/2017/05/26/20/jumlah-penduduk-banyaknya-rumah-tangga-dan-rata-rata-banyaknya-anggota-rumah-tangga-menurut-kecamatan-di-kota-pontianak-2014-2016.htmlÂ https://data.go.id/dataset?q=usaha+mikro&sort=score+desc%2C+metadata_modified+descÂ IFAC. (2005). â€œThe Roles and Domain of the Professional Accountant in Businessâ€. Information paper of Professional Accountants in Business CommitteeÂ Investopedia. (2018). â€œAccounting Cycleâ€. Accessed on 30 August 2018 at 14.20 https://www.investopedia.com/terms/a/accounting-cycle.aspÂ Ismail, Noor Azizi. (2009). â€œFactors Influencing AIS Effectiveness Among Manufacturing SMEs: Evidence From Malaysiaâ€. The Electronic Journal on Information System in Developing Countries; EJISDC 38, 10, 1-19Â Kariyoto. (2015). Analisis Implementasi Akuntansi Usaha Kecil dan Menengah. Thesis Vocational Education Universitas BrawijayaÂ Kementerian Keuangan. (2012). â€œKebijakan Antisipasi Krisis tahun 2012 Melalui Program Kredit Usaha Rakyatâ€. Badan Kebijakan FiskalÂ Warren, Reeve and Duchac. (2009). â€œAccounting 23th Editionâ€. USA: South-Western Cengage LearningÂ Mutmaniah, Dinda Audriene. (2016). â€œKontribusi UMKM Terhadap PDB Tembus Lebih dari 60 Persenâ€. Accessed on 15 January 2018 at 11.24 https://m.cnnindonesia.com/ekonomi/20161121122525-92-174080/kontribusi-umkm-terhadap-pdb-tembus-lebih-dari-60-persenÂ Rahmayuni, Siti. (2017). â€œPeranan Laporan Keuangan dalam Menunjang Peningkatan Pendapatan pada UKMâ€. Jurnal Sosial Humaniora dan Pendidikan Vol. 1 No. 1Â Rodhiyah. (2005). â€œKajian tentang Akuntabilitas Usaha Kecil Menengah Melalui Laporan Keuangan (Studi Kasus pada UKM Konveksi di Semarangâ€. Thesis Business Administration Diponegoro UniversityÂ Romney, Marshal B; and Steinbart, Paul J. (2012). Accounting Information System: Twelfth Edition. England: Pearson Education LimitedÂ Setyaningrum, Anis; Hakim, Abdul; and Sukanto (2009). â€œKeefektifan Pemberlakuan Surat Ijin Usaha Perdagangan (SIUP) bagi Pemberdayaan Usaha Kecilâ€. Jurnal Administrasi Publik (JAP); Vol. 1 No. 5Â Smirat, Belal Yousef AL. (2013). â€œThe Use of Accounting Information by Small and Medium Enterprises in South District of Jordan; (An empirical study)â€. IISTE: Research Journal of Finance and Accounting Vol. 4 No. 6Â Subramanyam, K. R. (2009). â€œFinancial Statement Analysis 10th Editionâ€. New York: McGraw-Hill/ Irwin.Â Van Auken, Howard; Ascigil, Semra; and Carraher, Shawn (2017). â€œTurkish SMEsâ€™ Use of Financial Statements for Decision Makingâ€. The Journal of Entrepreneurial Finance: Vol. 19 Iss. 1Â Van Auken, Howard; and Carraher, Shawn (2013). â€œInfluences on Frequency of Preparation of Financial Statements Among SMEsâ€. IOWA STATE University Digital Repository: Management PublicationsÂ Van Auken, Howard; and Kui Yang. (2014). Chinese SMEsâ€™ Uses of Financial Statements to Make Decisions.Â Vidarbha. (2014). â€œComputerized Accountingâ€. Accessed on 30 August 2018 at 14.15. https://vidarbhastudents.com/note/computerized-accounting/Â Wahyuningsih, Sri. (2009). â€œPeranan UKM Dalam Perekonomian Indonesiaâ€. MEDIAGRO Vol. 5 No. 1Â Walther, Larry M; and Skousen, Christopher J. (2009). â€œThe Accounting Cycleâ€. Ventus Publishing ApSÂ Wibowo, Teguh Imam. (2016). â€œ41 Persen UMKM di Pontianak Miliki Izinâ€. Accessed 6 February 2018 at 13.32 https://kalbar.antaranews.com/berita/345273/41-persen-umkm-di-pontianak-miliki-izinZikmund, William G. (2003). â€œResearch Method: Basic Data Analysis: Descriptive Statisticsâ€. Online Power Point of Health Economics Research Method